1971
DOI: 10.2135/cropsci1971.0011183x001100050030x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Selection in Successive Generations of Maize Inbred Progenies for Improvement of Hybrid Yield1

Abstract: The F1, F2, F3, and F4 generations of 20 selected maize (Zea mays L.) inbred families were evaluated by testcross performance to determine the efficacy of selection in three successive segregating generations to improve combining ability for yield. Ten lines had high yield performance and 10 lines had low yield performance as determined by testcrosses of the F5 or F6 generation. The high‐performance families had F2's equal to, or better than, their F1 source, and nine families were improved by selection in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Reducing the number of testcrosses that must be produced and evaluated would allow reduction in phenotyping costs and permit more testcross resources to be expended on evaluating lines already likely to have acceptable levels of tolerance. Under both high plant density (El-Lakany and Russell, 1971) and low soil N (Presterl et al, 2002) LP has been positively correlated with TP; however, under drought stress there have been conflicting reports of the ability of LP to predict TP. Earlier studies under nonstress conditions indicated that grain yield of hybrids could not be predicted from LP and therefore the evaluation of TP was necessary (for review see Hallauer et al, 2010).…”
Section: Relationship Of Line Per Se and Testcross Performance For Grmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the number of testcrosses that must be produced and evaluated would allow reduction in phenotyping costs and permit more testcross resources to be expended on evaluating lines already likely to have acceptable levels of tolerance. Under both high plant density (El-Lakany and Russell, 1971) and low soil N (Presterl et al, 2002) LP has been positively correlated with TP; however, under drought stress there have been conflicting reports of the ability of LP to predict TP. Earlier studies under nonstress conditions indicated that grain yield of hybrids could not be predicted from LP and therefore the evaluation of TP was necessary (for review see Hallauer et al, 2010).…”
Section: Relationship Of Line Per Se and Testcross Performance For Grmentioning
confidence: 99%
“…Earlier studies under nonstress conditions indicated that grain yield of hybrids could not be predicted from LP and therefore the evaluation of TP was necessary (for review see Hallauer et al, 2010). Under both high plant density (El-Lakany and Russell, 1971) and low soil N (Presterl et al, 2002) LP has been positively correlated with TP; however, under drought stress there have been conflicting reports of the ability of LP to predict TP. Betrán et al (1997) showed that LP under severe drought stress was strongly correlated with TP.…”
mentioning
confidence: 99%
“…Maize breeding methodologies and philosophies have not remained static during the hybrid era. Breeding philosophies and practices have evolved; incorporating scientific advances in breeding and genetic theory such as early‐generation testing (first proposed by Sprague in 1946 [c.f., Troyer, 2004]) (El‐Lakany and Russell, 1971); rapidly adopting improvements in agronomic management practices such as increased plant population densities and modern herbicide chemistries; and recognizing how best to assess genetic potential of a genotype through improvements in experimental design and data analysis. Changes such as adoption of improved management practices impacted both inbred line development and hybrid commercialization, while other changes were geared toward one of the two maize breeding activities.…”
Section: Source–sink Relationshipmentioning
confidence: 99%
“…Twenty inbred families from the study of Russell and Teich were ex amined further in testcross evaluations by El-Lakany and Russell (1971).…”
Section: Visual Selection Studiesmentioning
confidence: 99%